2013
DOI: 10.1021/cm4029484
|View full text |Cite
|
Sign up to set email alerts
|

Oligo(aryleneethynylene)s with Terminal Pyridyl Groups: Synthesis and Length Dependence of the Tunneling-to-Hopping Transition of Single-Molecule Conductances

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
173
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 116 publications
(188 citation statements)
references
References 53 publications
9
173
2
Order By: Relevance
“…[24,25] Electronic conduction through OPE wires anchored in metal-molecule-metal junctions has also been reported, with length dependent tunneling-to-hopping transitions observed. [26,27] In the present investigation we focus on a new series of five D-B-A complexes 1-5…”
Section: Extensive Studies Have Focused On Covalently-linked Donor-brmentioning
confidence: 99%
“…[24,25] Electronic conduction through OPE wires anchored in metal-molecule-metal junctions has also been reported, with length dependent tunneling-to-hopping transitions observed. [26,27] In the present investigation we focus on a new series of five D-B-A complexes 1-5…”
Section: Extensive Studies Have Focused On Covalently-linked Donor-brmentioning
confidence: 99%
“…[1][2][3] Nowadays there is intense interest in utilising these patterns in the optimisation of single-molecule device performance. Indeed, electrons passing through single molecules have been demonstrated to remain phase coherent, even at room temperature [3][4][5] and a series of theoretical and experimental studies have shown that their room-temperature electrical conductance is influenced by quantum interference (QI). [6][7][8][9][10][11][12][13][14][15][16][17][18][19] In practice, the task of identifying and harnessing quantum effects is hampered, because transport properties are strongly affected by the method used to anchor single molecules to electrodes [20][21][22][23][24][25][26][27][28][29][30] .…”
Section: Introductionmentioning
confidence: 99%
“…Given the close proximity to the Au surface, the slightly reduced steric bulk of a pyridine lone pair versus a benzene hydrogen atom could mean that more molecular conformations are possible within the Au–SAM–probe ensemble in the pyridine case. The extent of electronic coupling between the Au surface and the conductive backbone through the pyridine nitrogen, a known anchor group, could vary significantly with conformation, thus affording a broad conductance distribution.…”
Section: Resultsmentioning
confidence: 99%